Long-term clinical outcome and the identification of homozygous gene mutations in a patient with vitamin D hydroxylation-deficient rickets type 1A - Ja Hyang Cho; Eungu Kang; Gu-Hwan Kim; Beom Hee Lee; Jin-Ho Choi; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2016)
Vitamin D hydroxylation-deficient rickets type 1A (VDDR1A) is an autosomal recessively-inherited disorder caused by mutations in CYP27B1 encoding the 1α-hydroxylase enzyme. We report on a female patient with VDDR1A who presented with hypocalcemic seizure at the age of 13 months. The typical clinical and biochemical features of VDDR1A were found, such as hypocalcemia, increased alkaline phosphatase, secondary hyperparathyroidism and normal 25-hydroxyvitamin D3 (25(OH)D3). Radiographic images of the wrist showed metaphyseal widening with cupping and fraying of the ulna and distal radius, suggesting rickets. A mutation analysis of the CYP27B1 gene identified a homozygous mutation of c.589+1G>A in the splice donor site in intron 3, which was known to be pathogenic. Since that time, the patient has been under calcitriol and calcium treatment, with normal growth and development. During the follow-up period, she did not develop genu valgum, scoliosis, or nephrocalcinosis.